MARKETING STRATEGY INNOVATION IN THE FRAMEWORK TOWARDS EXPANSION OF DIGITAL BANK ACCESS AROUND STUDENTS (A CASE STUDY ON BLU BCA) - Wijaya, Septihani Michella; Putri, Angely Olivia; Wijaya, Andi (International Journal of Application on Economics and Business, 2023)
Blu is a mobile banking service from BCA Digital which is designed and developed to make it easier for its customers to make financial and non-financial transactions via mobile phones. Currently, Blu already has a BI Fast Payment system for its services. BI Fast Payment is infrastructure. A national retail Payment System that can facilitate retail payments in real-time, safe, efficient, and available at any time. With the BI Fast Payment system, customers can make inter-bank transfers more efficiently and effectively than usual, which is IDR 2,500 per transaction. Not only can it be used to make payments, Blu can also be used for various purposes related to banking with various features such as: Blu Account for making purchases and withdrawals, Blu Saving for saving, Blu Gether which can plan finances with other users, and Blu Deposit opens a time deposit service of at least IDR 1,000,000. Due to the Covid-19 pandemic, the use of digital banks is increasing in Indonesia due to the cashless system when making payments. Therefore, Blu is here to support the system. Blu still has many systems and features that need to be developed to make users more comfortable.